2012
DOI: 10.3901/jme.2012.21.084
|View full text |Cite
|
Sign up to set email alerts
|

Gear Transmission Fault Diagnosis Based on the Bispectrum Analysis of Induction Motor Current Signatures

Abstract: Abstract:Motor current signal analysis has been an effective way for many years to monitor electrical machines.However, little research work has been reported in using this technique for monitoring their downstream equipment due to difficulties in extracting weak fault signals in a noisy measured current signal. This paper investigates the characteristics of electrical current signals measured from an induction motor for monitoring faults from a downstream gear transmission system by a novel modulation signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Bispectrum analysis is a useful signal processing tool that has shown significant benefits over traditional spectral analyses due to its unique properties of nonlinear system identification, Gaussian noise elimination, and phase information retention [14][15][16][17][18][19][20][21]. Conventional bispectrum (CB) was applied to vibration signals for the detection of different degrees of tooth breakage of a two-stage helical gearbox and tooth crack [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bispectrum analysis is a useful signal processing tool that has shown significant benefits over traditional spectral analyses due to its unique properties of nonlinear system identification, Gaussian noise elimination, and phase information retention [14][15][16][17][18][19][20][21]. Conventional bispectrum (CB) was applied to vibration signals for the detection of different degrees of tooth breakage of a two-stage helical gearbox and tooth crack [15].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional bispectrum (CB) was applied to vibration signals for the detection of different degrees of tooth breakage of a two-stage helical gearbox and tooth crack [15]. Chen et al [16] introduced MSB, which is a significant improvement of the CB in that it enhanced CB to apply the modulation signal efficiently. The results showed reliable fault diagnosis and revealed that random noise can be suppressed effectively, being much better than that of the power spectrum (PS) and CB for diagnosing different seeded faults, such as tooth breakage and shaft misalignment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas through the second path, the vibration signal follows a longer path, from its origin to the shaft firstly, then from the shaft go through the sun gear, planet gear and ring gear, after that from the ring gear to the gearbox casing, and finally to the sensor. Therefore, the vibration signal will be amplitude modulated by both sun gear rotating frequency and carrier rotating frequency as shown in (14).…”
Section: Characteristic Frequencies For Bearing Faultmentioning
confidence: 99%
“…According to the references [10][11][12][13][14][15], MSB is an effective demodulation technique and demonstrated to be able to detect bearing faults under heavy noise influences, Based on Fourier transform   Xf of a vibration signal x , MSB is defined as the following equation.…”
Section: A Definition Of Msbmentioning
confidence: 99%
“…Gu et al named this method as the Modulation Signal Bispectrum (MSB) analysis and achieved fault diagnosis of downstream mechanical equipment using electrical motor current signals in 2011 [10]. After that, their team continues to deeply study and analyse the method to achieve a series of achievements [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%